Media Exchange Performance Test Using the Bradford Assay in an Automated Bioreactor Engineering Model for Space Experiments. (April 2019) - Lee, Jong-Won; Ha, Kyoung-Bong; Kim, Youn-Kyu; Lee, Joo-Hee; Choi, In-Ho; Park, Seul-Hyun
Life science research has been actively carried out in space for a long time using bioreactor equipment, in anticipation of manned space exploration and space tourism. Such studies have reported that the microgravity environment has a negative effect on the human body, including the musculoskeletal system, nervous system, and endocrine system. Bone loss and muscular atrophy are issues that need to be resolved before long-term exposure of the human body to a space environment. To address this problem, Y. K. Kim et al. designed a system in 2015 and performed an evaluation of an automated bioreactor development model (DM) for space experiments. In this study, we developed an automated bioreactor engineering model (EM) based on the previous literature, and conducted media exchange performance testing using the Bradford assay. We used a novel method that allowed quantitative assessment of the media exchange rate versus the conventional assessment method using visual observation with a camera. By measuring the media exchange rate of the automated bioreactor EM, we attempted to verify applicability for the system for space experiments. We expect that the experimental method proposed in this study is useful for logical determination of liquid exchange or circulation in different closed systems.